Pemberantasan Tindak Pidana Korupsi di Indonesia: Masalah dan Solusinya - SALSADILA, NURANNISA; Efritadewi, Ayu; Widiyani, Heni (Indonesian Journal of Law and Justice, 2023)
In Indonesia, corruption is a big problem that endangers many aspects of national, state and social life. Corruption has harmed the internal and external environment of the perpetrators and resulted in material losses. Harmonious laws, international cooperation, integrated law enforcement, and active community participation are needed to resolve this problem. Apart from that, challenges in eradicating corruption must be overcome, such as by increasing training and education and implementing moral values. The aim of this research is to understand the characteristics of normative legal knowledge, understand, explain and apply legal regulations and the principles that guide them. The method used is a normative juridical approach, namely a type of legal research carried out by analyzing secondary data or raw materials. Corrupt practices must be actively avoided, and corruption courts must play a proactive role in eradicating corruption. The results of this research are firm law enforcement, eradicating gratification, increasing transparency and accountability, as well as increasing public legal and ethical awareness. Cooperation is needed from various parties, including the government, law enforcement agencies and the community, to jointly overcome this corruption problem. It is hoped that with extensive efforts, the negative impacts of corruption can be reduced and a transparent and clean government can be created.